Toddlers’ Unintentional Injuries: The Role of Maternal-Reported Paternal and Maternal Supervision* - Damashek, Amy (Oxford University Press, 2013)
Research indicates that mothers’ supervision protects children from injuries. However, little research has examined the role of fathers’ supervision in children’s injuries. Objectives This study compared the role of maternal and paternal supervision in children’s injury risk and severity using maternal reports. Methods Mothers (n = 170) of toddlers were interviewed for 6 months about their children’s unintentional injuries. Results Children were more likely to engage in high activity levels and were at higher risk for injury when being cared for by their fathers. Although higher supervision predicted lower injury risk for both mothers and fathers, fathers’ close supervision (as reported by mothers) was a stronger predictor of injury risk than mothers’ supervision. Conclusion Children’s higher levels of activities may have accounted for their higher risk of injury when in their fathers’ care. These findings indicate the need to include fathers in injury prevention efforts.